Drivers of government restrictions on humanitarian supply chains: An exploratory study. Issue 3 (5th December 2016) - Kunz, Nathan; Reiner, Gerald
Abstract : Purpose: Foreign governments do not always welcome international humanitarian organizations responding to a disaster in their country. Many governments even impose restrictions on humanitarian supply chains through import barriers, travel restrictions or excessive bureaucracy. The purpose of this paper is to analyze these restrictions and try to identify the government characteristics that best explain the tendency to impose such restrictions. Design/methodology/approach: Through a multiple case study among four international humanitarian organizations the authors identify and analyze the restrictions imposed on humanitarian supply chains in 143 different programs. The authors compare the average number of restrictions per country with different governmental and socio-economic situational factors. Findings: The authors find that state fragility, a combination of government ineffectiveness and illegitimacy, is the characteristic that best explains the tendency of a government to impose restrictions on humanitarian supply chains. Practical implications: Knowing that fragile states tend to impose a high number of restrictions helps humanitarian organizations to prepare adequately before entering a country with a fragile government. The organization can, for example, anticipate possible concerns and establish trust with the government. Commercial companies starting to do business in such country can learn from this knowledge. Originality/value: Multiple studies have mentioned the strong impact of governments on humanitarian supply chains, but no paper has yet analyzed this problem in detail. The paper is the first to identify the characteristics that explain the number of restrictions governments impose on humanitarian supply chains, and what humanitarian organizations can do to address them.